Development of a Dynamic Simulation Model for Equalization Tanks - Simo, Eugene Fotso (Department of Civil Engineering, 2022)
The influent to a water and resource recovery facility (WRRF) generally exhibits significant diurnal variations in flow rate and load concentration. This makes determining the operating parameters and subsequently the overall operation of plants difficult, especially in developing countries due to the lack of highly skilled operators. Hence, there is an incentive for the control and operation of WRRFs in developing countries to be improved. Flow equalization tanks were identified as a potential method to attenuate the diurnal variations in flow rate and load concentration into plants. The main aim of this research was to develop a viable dynamic simulation model for the operation of flow equalization tanks, within a plant-wide framework (to allow for the evaluation of design and control strategies). The next aim was to determine the benefits of equalization tanks towards design and optimised operation of future WRRFs via scenario analyses. Finally, the effects of the equalization tank on the performance of various unit processes in a WRRF were to be investigated. The model was developed in three steps; i) the development of the required equations to model equalization tanks, ii) mass balance throughout the model for internal consistency and iii) scenario analyses to determine if the model generated reasonable and scientifically sound outputs. The model was developed using Microsoft Excel Visual Basic (VBA) and WEST®. Two scenarios were considered to assess the equalization tank modelled. Scenario One involved the comparison of the capital cost, unit process sizes and total footprint of a balanced sludge age Modified Ludzack-Ettinger (MLE) system with and without an equalization tank. Scenario Two compared the plant performance of the MLE system designed in Scenario One with and without a flow equalization tank. A dynamic simulation model replicating equalization tanks was successfully developed. From scenario analyses, it was determined that using an MLE system and only considering equalization of flow, there was a reduction in the size of several unit processes by 8-9% (primary settling tank, biological reactors, secondary settling tank, flotation unit, anoxic-aerobic digester), due to the less conservative design values that could be used as the variations of the influent were decreased. Despite this, a 13% overall increase in the footprint of the WRRF was observed due to the addition of the equalization tank. The attenuation of diurnal flow variations also resulted in reduction of various plant parameters by up to 50% (flow, OUR, VSS flux). Finally, there was a 10% improvement in the performance of various unit processes due to the presence of the equalization tank. In conclusion, the inclusion of equalization tanks in WRRFs has significant positive effects. These results were obtained with equalization of flow only. Some other limitations were experienced during the project resulting in the following recommendations: further research will be needed to validate and calibrate the model, As the model was not successfully incorporated in a plant-wide framework, further developments in that direction are required, as well as including the equalization of load in the model.